Between individual rights and collective sustainability: Judicialization of access to medicines in the Unified Health System (UHS) (Research, Society and Development, 2025)
This study conducted a systematic review to analyze the current landscape of the judicialization of healthcare in Brazil, particularly regarding the provision of medication within the Unified Health System (SUS). Based on the 1988 Federal Constitution and the Organic Health Law (Law No. 8,080/1990), the right to health was enshrined as a duty of the State, encompassing the distribution of medication. However, structural limitations, historical underfunding, and poor administrative management have compromised the effectiveness of this right, generating a growing demand for lawsuits. The results showed that over 60% of the lawsuits analyzed were granted, with cases predominantly related to chronic, neurological, and degenerative diseases, generally handled by the Public Defender's Office. It was observed that, although judicialization guarantees the fulfillment of the individual right to health, it also has negative impacts on SUS financing, such as the withholding of funds and the weakening of collective policies. On the other hand, it plays a driving role in updating the National List of Essential Medicines (RENAME), pressuring the government to incorporate new therapies. The conclusion is that judicialization should be understood as a multifaceted phenomenon, capable of revealing structural weaknesses in the SUS (Unified Health System) and, at the same time, fostering its improvement, requiring greater planning, transparency, and dialogue among administrators, health professionals, the judiciary, and civil society.